A defined synthetic substrate for serum-free culture of human stem cell derived cardiomyocytes with improved functional maturity identified using combinatorial materials microarrays - Patel, Asha K.; Celiz, Adam D.; Rajamohan, Divya; Anderson, Daniel G.; Langer, Robert; Davies, Martyn C.; Alexander, Morgan R.; Denning, Chris (Elsevier, 2015)
Cardiomyocytes from human stem cells have applications in regenerative medicine and can provide models for heart disease and toxicity screening. Soluble components of the culture system such as growth factors within serum and insoluble components such as the substrate on which cells adhere to are important variables controlling the biological activity of cells. Using a combinatorial materials approach we develop a synthetic, chemically defined cellular niche for the support of functional cardiomyocytes derived from human embryonic stem cells (hESC-CMs) in a serum-free fully defined culture system. Almost 700 polymers were synthesized and evaluated for their utility as growth substrates. From this group, 20 polymers were identified that supported cardiomyocyte adhesion and spreading. The most promising 3 polymers were scaled up for extended culture of hESC-CMs for 15 days and were characterized using patch clamp electrophysiology and myofibril analysis to find that functional and structural phenotype was maintained on these synthetic substrates without the need for coating with extracellular matrix protein. In addition, we found that hESC-CMs cultured on a co-polymer of isobornyl methacrylate and tert-butylamino-ethyl methacrylate exhibited significantly longer sarcomeres relative to gelatin control. The potential utility of increased structural integrity was demonstrated in an in vitro toxicity assay that found an increase in detection sensitivity of myofibril disruption by the anti-cancer drug doxorubicin at a concentration of 0.05 μM in cardiomyocytes cultured on the co-polymer compared to 0.5 μM on gelatin. The chemical moieties identified in this large-scale screen provide chemically defined conditions for the culture and manipulation of hESC-CMs, as well as a framework for the rational design of superior biomaterials.